Effect of Force 6® Poultry (Curcumin) on Lipid profile in Broiler chicken in presence of IBD vaccine: Amjed H. Ulaiwi1, Shony M. Odishio2 and Salah M. Hassan3 - Ulaiwi, Amjed H. (The Iraqi Journal of Veterinary Medicine, 2015)
The aim of this study was to investigate effect of Force 6® Poultry on lipid profile in broiler chicken in presence of IBD vaccine. Two hundred chicks at one day old were divided into four equal groups as: Group 1; 50 day old unvaccinated chicks were given (50 gm/ton) of Force 6® Poultry (curcumin) along the experimental period (35 days), chicks in group 2; were given IBD vaccine in (15-day old) (BURSINE-2), chicks in group 3 were vaccinated with IBD at (15-day old) and given Force 6® Poultry along time of experimental (with 50 gm/ton). Group 4, 50 chicks were saved as negative control. Blood samples were collected from heart for lipid profile detection and included (cholesterol, triglyceride, high-density lipoprotein HDL, very low density lipoprotein VLDL, low-density lipoprotein LDL). The result of lipid profile showed significant (P˂0.05) differences with higher value between groups which were (G2, G4) which did not receive force 6 poultry than group (G1, G3) which received force 6 poultry for (cholesterol, triglyceride, HDL, LDL,VLDL). In conclusion, the Force 6® Poultry had main effect to improve lipid profile of treated groups than these groups untreated.